Imaging local brain activity of multiple freely moving mice sharing the same environment - Inagaki, Shigenori; Agetsuma, Masakazu; Ohara, Shinya; Iijima, Toshio; Yokota, Hideo; Wazawa, Tetsuichi; Arai, Yoshiyuki; Nagai, Takeharu (Scientific reports, 2019)
Electrophysiological field potential dynamics have been widely used to investigate brain functions and related psychiatric disorders. Considering recent demand for its applicability to freely moving subjects, especially for animals in a group and socially interacting with each other, here we propose a new method based on a bioluminescent voltage indicator LOTUS-V. Using our fiber-free recording method based on the LOTUS-V, we succeeded in capturing dynamic change of brain activity in freely moving mice. Because LOTUS-V is the ratiometric indicator, motion and head-angle artifacts were not significantly detected. Taking advantage of our method as a fiber-free system, we further succeeded in simultaneously recording from multiple independently-locomotive mice that were freely interacting with one another. Importantly, this enabled us to find that the primary visual cortex, a center of visual processing, was activated during the interaction of mice. This methodology may further facilitate a wide range of studies in neurobiology and psychiatry.